Optimization of the Structure of Marketing Complex Costs as a Means of Business Sustainable Development - Rutkauskas, Aleksandras Vytautas; Stasytytė, Viktorija; Ginevičius, Adomas (Ekonomika, 2007)
Business development and marketing interactions and especially a quantitative evaluation of the direct relation and feedback becomes a crucial problem in forming rational marketing and business development budgets. The formulation of the mentioned problem, analysis and decisions most often are implemented on the basis of the business development and marketing projects.For a long time marketing has dispensed with quantitative and optimization researches. It was caused by the fact that empirical experience, as well as marketing departments’ perception was discovering the sources of effectiveness, that were guaranteeing an increasing financial efficiency of marketing. However, with the expansion of globalization, local sources - the only sources that are known to local marketers - deplete. Thus, global competitiveness develops forces searching for the methods of marketing subsystems’ interaction in order to achieve the integrated effect of the marketing system.There is a need for marketing, as well as for other business components to form a cost-benefit budget and search for the methods and means of budget optimization. This is a complex problem, because marketing does not possess a common concept of how to measure the effectiveness of the separate marketing means. The same could be applied to the main means of the marketing complex structure - price, product, place, promotion, as well as to the detailed elements composing these means. Quantitative evaluation of the efficiency of these complexes and the optimal distribution of funds among them should become a strategic marketing efficiency development provision.